In Vitro Evaluation of Inflow Cannula Fixation Techniques in Left Ventricular Assist Device Surgery. Issue 3 (18th April 2016) - Hanke, Jasmin S.; Krabatsch, Thomas; Rojas, Sebastian V.; Deniz, Ezin; Ismail, Issam; Martens, Andreas; Shrestha, Malakh; Haverich, Axel; Netuka, Ivan; Schmitto, Jan D.
Abstract: The therapy of terminal heart failure with left ventricular assist devices has become a standard in cardiac surgery. Yet the surgical implantation technique is not standardized and differs from center to center. Complications associated with left ventricular assist device (LVAD) inflow cannula placement are thrombosis, suction events, and flow disturbances. Within this in vitro study we aimed to investigate if the fixation technique of the sewing ring has an impact on the position of the inflow cannula. For this in vitro study the HeartMate III LVAD (Thoratec Corporation, Pleasanton, CA, USA) was used. In five sessions, two approaches were considered for coring of the ventricle for LVAD inflow cannula insertion: "sew‐then‐core" and "core‐then‐sew." In the "sew‐then‐core" technique, the sewing cuff is first affixed to the heart, usually with 8–16 interrupted pledgeted mattress sutures. Subsequently, a cylindrical knife is used to resect a cylindrical core of myocardium to permit cannula insertion. In the "core‐then‐sew" technique, the sequence is reversed such that the knife is used before the suture ring is affixed. When the "sew‐then‐core" technique is used, the mattress sutures may be placed with full‐thickness bites that penetrate the endocardium (i.e., transmural stitching) or partial‐thickness bites that do not penetrate the endocardium (i.e., epicardial stitching). When the "core‐then‐sew" technique is used, the suture is passed fully into the ventricular lumen and fed back through the cored hole, at which point the needle may be reinserted into the freshly cored myocardium such that it exits the epicardium (i.e., transmural stitching with back stitch) or not (i.e., transmural stitching without back stitch). These four different sewing ring fixation suturing techniques were tested by experienced surgeons to affix the sewing ring: transmural stitching, epicardial stitching, transmural stitching with back stitch, and transmural stitching without back stitch. The sewing ring was sewed onto a silicone dummy designed to simulate the left ventricle with standard 2–0 Ethibond sutures (Ethicon, Somerville, NY, USA). Afterward, the dummies were measured and documented via photography. In addition, porcine hearts were used to simulate the suturing techniques in a physiological setting. The setting of the inflow cannula is substantially influenced by the fixation method of the sewing ring. Epicardial stitching showed the best results with stable cannula fixation, minimal gap around the cannula and no contact between the sutures and sewing ring with blood. The method of transmural stitching without back stitch showed the worst results by creating the biggest epithelial gap between inflow cannula and tissue as well as proving the biggest surface for blood contact between sewing ring and sutures. In general, both "sew‐then‐core" techniques resulted in a greater degree of apposition between the cuff and epicardial tissue. Within the study we revealed that the surgical fixation of the sewing ring has a significant impact on the inflow cannula stability, position, and tissue apposition in LVAD implantation surgery. Epicardial stitching of the sewing ring provides the best results in order to prevent suction events as well as thrombosis formation.